Mastitis bovina : estudios moleculares, fenotípicos y biológicos de estafilococos coagulasa negativa - Srednik, Mariela Elizabeth (2017)
Bovine mastitis is considered one of the main causes of economic losses in dairy cows. Although it is caused by several etiological agents, in recent years\nthe prevalence of coagulase-negative staphylococci (CNS) has increased worldwide, being considered an emerging pathogen. Recent studies show that microorganisms among the CNS group have the ability to form biofilm and\nbecause of that, they could persist in the mammary gland. It is important to\nhighlight the implications to public health, since CNS are reservoirs of resistance genes. The objective of this study was to evaluate the antimicrobial susceptibility and the presence of resistance genes to antimicrobial agents\ncommonly used in bovine mastitis therapeutics. Furthermore, to evaluate biofilm formation, enzymatic treatments of biofilms formed by CNS, and the presence of virulence genes in CNS isolates from bovine mastitis from different dairy\nherds in Argentina. 138 CNS isolates were identified at the species level by\nrestriction fragment length polymorphism (RFLP) analysis of the gap gene. The most prevalent CNS species were staphylococcus chromogenes (n=59,\n42.8%), Staphylococcus epidermidis (n=19, 13.8%) and Staphylococcus\ndevriesei (n=12, 8.7%).\nGenes encoding resistance to ?-lactams (n=26; 28.8%) were detected among\nthe isolates: blaZ (n=28, 20.3%), mecA (n=4, 2.9%) and mecC (n=1, 0.7%).\nResistance to macrolides and lincosamides (n=14, 10.1%) was attributable \nermC (n=9, 6.5), ermB (n=6, 4.3), mphC (n=5, 6%) and mrsA (n=3, 2.2%),\nalone or in a combination of those genes.\n\nThe majority (93.5%) of isolates was able to form biofilms. Among the biofilm-\npositive isolates, 37.2%, 11.6% and 51.2% were strong, moderate and weak\nbiofilm formers, respectively. The ability to form biofilms varied among CNS\nspecies. S. haemolyticus and S. devriesei isolates formed significantly more\nbiofilms than other species. Enzymatic treatment results suggest that proteins\nand eDNA play a larger role in the structural integrity of CNS biofilms. icaA\n(n=9, 6.5%), bap (n=5, 3.6%) and aap (n=5, 3.6%) were detected in a few\nisolates, while atlE (n=38, 27.5%), embP (n=35, 25,4%) and fbe (n=20, 14.4%) were detected in a considerable number of CNS. The eno gene (n=122, 88.4%) was present in the majority of isolates.\nThe results obtained show differences in the ability of biofilm formation among\nCNS species and there are intra-species variations. Although antimicrobial\nresistance to common antibiotics is low, it is important to highlight the presence of methicillin-resistant CNS carrying the mecA/C genes, important for the public health implications, since CNS are reservoirs of resistance genes. In this study,\nwe identified CNS species involved in mastitis and provide information about\npathogenicity and antimicrobial resistance, which is essential to design efficient strategies to control mastitis caused by CNS.\nFuture studies should be carried out to examine the association of biofilm\nformation with treatment failure and the occurrence of persistent intramammary\ninfections by different CNS species in cattle.